Can a Proper T-Cell Development Occur in an Altered Thymic Epithelium? Lessons From EphB-Deficient Thymi - Muñoz, Juan José; García-Ceca, Javier; Montero-Herradón, Sara; Sánchez del Collado, Beatriz; Alfaro, David; Zapata, Agustín (Frontiers in Endocrinology, 2018)
For a long time, the effects of distinct Eph tyrosine kinase receptors and their ligands, ephrins on the structure, immunophenotype and development of thymus and their main cell components, thymocytes (T) and thymic epithelial cells (TECs) have been studied. In recent years, the thymic phenotype of mutant mice deficient in several Ephs and ephrins B has been determined. Remarkably, thymic stroma in these animals exhibits important defects that appear early in ontogeny but little alterations in the proportions of distinct lymphoid cell populations. In the present review, we summarize and extend these results discussing possible mechanisms governing phenotypical and functional thymocyte maturation in an absence of the critical T-TEC interactions, concluding that some signaling mediated by key molecules, such as MHCII, CD80, β5t, Aire, etc could be sufficient to enable a proper maturation of thymocytes, independently of morphological alterations affecting thymic epithelium.